Frond reconstruction of Polymorphopteris mei sp. nov. from the early Permian Wuda Tuff Flora with insights into its taphonomy - Li, Dan Dan; Zhou, Wei Ming; Clements, Thomas; Hilton, Jason; Wang, Shi Jun; Wu, Yi Fei; Sun, Wen Jun; Wang, Jun (Historical Biology, 2026)
Ancient forests preserved in growth position by rapid sedimentological burial (T0 assemblages) constitute exceptionally valuable fossil repositories, especially those covered by fine-grained volcanic ash (tuff) that may preserve plant morphology and anatomy in high-fidelity. This study documents the frond morphology and anatomy of a new species, Polymorphopteris mei sp. nov. from the Wuda Tuff Flora, an in situ fossil forest Lagerstätte of early Permian age from Inner Mongolia, China preserved by volcanic ash. The frond of P. mei is tripinnate, composed of three types of penultimate pinnae and three types of ultimate pinnae. Anatomical features of the frond and penultimate rachises correspond to the stewartiopterid-type leaf trace configuration characteristic of the Marattiales fern evolutionary stem-group family Psaroniaceae. Pyrite-infilled pore-like structures within the rachises are identified as possible evidence of post-mortem fungal action. This study enhances our understanding of the morphology, anatomy, systematic affinity and taphonomy of P. mei and its ecological context in the early Permian peat-forming communities of Cathaysia.
CRIS-Team Scopus Importer:2026-01-23
Keywords: anatomy; marattialean fern; T; taphonomy; Wuda Tuff Flora